Fusion Toxin BLyS-Gelonin Inhibits Growth of Malignant Human B Cell Lines In Vitro and In Vivo - Luster, Troy A.; Mukherjee, Ipsita; Carrell, Jeffrey A.; Cho, Yun Hee; Gill, Jeffrey; Kelly, Lizbeth; Garcia, Andy; Ward, Christopher; Oh, Luke; Ullrich, Stephen J.; Migone, Thi-Sau; Humphreys, Robin (PLOS ONE, 2012)
B lymphocyte stimulator (BLyS) is a member of the TNF superfamily of cytokines. The biological activity of BLyS is mediated by three cell surface receptors: BR3/BAFF-R, TACI and BCMA. The expression of these receptors is highly restricted to B cells, both normal and malignant. A BLyS-gelonin fusion toxin (BLyS-gel) was generated consisting of the recombinant plant-derived toxin gelonin fused to the N-terminus of BLyS and tested against a large and diverse panel of B-NHL cell lines. Interestingly, B-NHL subtypes mantle cell lymphoma (MCL), diffuse large B cell lymphoma (DLBCL) and B cell precursor-acute lymphocytic leukemia (BCP-ALL) were preferentially sensitive to BLyS-gel mediated cytotoxicity, with low picomolar EC50 values. BLyS receptor expression did not guarantee sensitivity to BLyS-gel, even though the construct was internalized by both sensitive and resistant cells. Resistance to BLyS-gel could be overcome by treatment with the endosomotropic drug chloroquine, suggesting BLyS-gel may become trapped within endosomal/lysosomal compartments in resistant cells. BLyS-gel induced cell death was caspase-independent and shown to be at least partially mediated by the “ribotoxic stress response.” This response involves activation of p38 MAPK and JNK/SAPK, and BLyS-gel mediated cytotoxicity was inhibited by the p38/JNK inhibitor SB203580. Finally, BLyS-gel treatment was shown to localize to sites of disease, rapidly reduce tumor burden, and significantly prolong survival in xenograft mouse models of disseminated BCP-ALL, DLBCL, and MCL. Together, these findings suggest BLyS has significant potential as a targeting ligand for the delivery of cytotoxic “payloads” to malignant B cells.